Characterization of Nigella sativa L. essential oil-loaded solid lipid nanoparticles - Alhaj, Nagi Ahmed; Shamsudin, Mariana Nor; Mohamed Alipiah, Norfarrah; Zamri, Hana Farizah; Abdul, Ahmad Bustamam; Ibrahim, Siddig; Abdullah, Rasedee (Science Publications, 2010)
Problem statement: Seeds of Nigella sativa L., commonly known as black seed, have been used in traditional medicine by many Asian, Middle Eastern and Far Eastern Countries to treat headache, coughs, abdominal pain, diarrhea, asthma, rheumatism and other diseases. The seeds of this plant are the most extensively studied, both phytochemically and pharmacologically. The aqueous and oil extracts of the seeds have been shown to possess especially nowadays in pharmaceutical antioxidant, anti-inflammatory, anticancer, analgesic, antimicrobial activities and medicinal and cosmetic applications, sanitary, cosmetic, agricultural and food industries.